Legal culture in contemporary Serbia: Structural analysis of attitudes towards the rule of law - Vuković Danilo; Cvejić Slobodan (Anali Pravnog Fakulteta u Beogradu)
The article analyzes the support for the rule of law among Serbian citizens. The research data show that support for the rule of law depends on the structural socio-economic position of respondents and their position on the transition winners and losers scale i.e., the level of fulfillment of their interests in the new system. There is differentiation among better educated respondents. Those who benefited from the new system recognize the importance of the rule of law. Others, due to their knowledge and understanding of the functioning of the system, are more disappointed and more critical towards it.